Neuroprotective Effects of Celastrol on Transient Global Cerebral Ischemia Rats via Regulating HMGB1/NF-κB Signaling Pathway - Zhang, Bo; Zhong, Qi; Chen, Xuhui; Wu, Xi; Sha, Rong; Song, Guizhi; Zhang, Chuanhan; Chen, Xiangdong (Frontiers in Neuroscience, 2020)
Cerebral ischemia is a major cause of brain dysfunction, neuroinflammation and oxidative stress have been implicated in the pathophysiological process of cerebral ischemia/reperfusion injury. Celastrol is a potent inhibitor of inflammation and oxidative stress that has little toxicity. The present study was designed to evaluate whether celastrol has neuroprotective effects through anti-inflammatory and antioxidant actions, and to elucidate the possible involved mechanisms in transient global cerebral ischemia reperfusion (tGCI/R) rats. Celastrol (1, 2 or 4 mg/kg) was administrated intraperitoneally immediately after reperfusion and the effect of celastrol on reverting spatial learning and memory impairment was determined by Morris water maze (MWM) task. Inflammatory response and oxidative stress, hippocampal neuronal damage and glial activation, and HMGB1/NF-κB signaling pathway proteins were also examined. Our results indicated that celastrol dose-dependently reduced hippocampal and serum concentration of pro-inflammatory markers (TNF-α, IL-1β and IL-6) and oxidative stress marker (MDA), whereas the anti-inflammatory marker IL-10 and antioxidant markers (GSH, SOD and CAT) were increased significantly in celastrol treated tGCI/R rats. Celastrol alleviated apoptotic neuronal death, inhibited reactive glial activation and proliferation and improved ischemia-induced neurological deficits. Simultaneously, we found that mechanisms responsible for the neuroprotective effect of celastrol could be attributed to its anti-inflammatory and antioxidant actions via inhibiting HMGB1/NF-κB signaling pathway. These findings provide a proof of concept for the further validation that celastrol may be a superior candidate for the treatment of severe cerebral ischemic patients in clinical practice in the future.